1998
DOI: 10.1016/s0092-8674(00)81477-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for Caspase 9 in Apoptotic Pathways In Vivo

Abstract: Mutation of Caspase 9 (Casp9) results in embryonic lethality and defective brain development associated with decreased apoptosis. Casp9-/- embryonic stem cells and embryonic fibroblasts are resistant to several apoptotic stimuli, including UV and gamma irradiation. Casp9-/- thymocytes are also resistant to dexamethasone- and gamma irradiation-induced apoptosis, but are surprisingly sensitive to apoptosis induced by UV irradiation or anti-CD95. Resistance to apoptosis is accompanied by retention of the mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
760
2
7

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,187 publications
(826 citation statements)
references
References 42 publications
55
760
2
7
Order By: Relevance
“…Several lines of evidence support the idea that caspase-9 is the essential caspase in many forms of apoptosis (Li et al, 1997b;Kuida et al, 1998;Hakem et al, 1998;Sun et al, 1999). In addition, although caspase-8 has been initially suggested to interact with Apaf-1, a more detailed analysis showed that caspase-9 is the only Apaf-1 interacting protease in living cells (Slee et al, 1999).…”
Section: Discussionmentioning
confidence: 88%
“…Several lines of evidence support the idea that caspase-9 is the essential caspase in many forms of apoptosis (Li et al, 1997b;Kuida et al, 1998;Hakem et al, 1998;Sun et al, 1999). In addition, although caspase-8 has been initially suggested to interact with Apaf-1, a more detailed analysis showed that caspase-9 is the only Apaf-1 interacting protease in living cells (Slee et al, 1999).…”
Section: Discussionmentioning
confidence: 88%
“…Because procaspase 9, procaspase 3, and PARP are associated with the apoptotic cell death pathway [37], we next examined their levels in guggulsterone-treated U937 cells.…”
Section: Guggulsterone Induces Cleavage Of Procaspase 9 Procaspase 3mentioning
confidence: 99%
“…The defect in the execution of apoptotic cell death was caused by the failure to initiate JNK-induced cytochrome c release from the mitochondria [204]. This malfunction is significant since it is critical for the subsequent sequential activation of Apaf-1 [120], the initiator-caspase caspase-9 [76] and finally the effector-caspase caspase-3 [217] all of which are essential in the execution of apoptosis. Tournier et al [204] suggested that the apoptotic response is suppressed in JNK null MEF due to the absence of JNK, which is needed to initiate the apoptotic cascade (Fig.…”
Section: Map Kinase Signalingmentioning
confidence: 99%